A cross-sectional investigation of trend in career specialty preference among clinical year medical undergraduates, including factors influencing preferences and discouragement - Dawood, Muhammad Hamza; Mir, Filza; Ahmed, Hajrah Hilal; Wasim, Mehmooda; Athar Khan, Muniba; Hasan, Ali; Islam, Umair Ul; Ahmed, Raheel (Frontiers in Medicine, 2025)
IntroductionSelecting a medical specialty is a crucial decision influenced by personal, professional, and societal factors. However, data on these determinants among clinical-year medical students in Pakistan remain scarce. This study seeks to identify the specialty preferences of clinical-year medical undergraduates in Pakistan and to elucidate the factors influencing their preference and discouragement decisions.MethodsThis investigation employed a cross-sectional survey methodology involving clinical-year medical students from September 16th, 2024, to November 10th, 2024 among both private and public medical colleges in Karachi. A total of 436 participants were randomly selected using a simple random sampling technique. Chi-square/Fisher’s Exact tests, were performed to analyze trends in career preferences, assess the association between specialty preferences and demographic variables, and identify factors influencing career preference and discouragement, both generally and within specific specialties and demographic categories.ResultsAmong the 430/436 respondents, 28.6% were male and 71.4% were female. 56.9% of males preferred surgery, while 52.7% of females favored medicine as their career choice. Students from private institutions exhibited a higher preference for surgery (51.3%) compared to government institution students, who favored medicine (53.1%). A notable preference for surgery was observed among 3rd-year students (37.2%), with a significant shift towards medicine by 5th-year students (42.8%) (P-value=0.002). The principal factors affecting career preference were own interest/passion (85%), vast-career opportunities (31.1%), and clinical rotations (29.7%). Major discouragement factors included lack of mentorship (76.3%), gender inequity (46.7%), and family obligations (31.6%). A comparable trend was observed across specialty, year of education, sex, and institutional sector for both career preference (P-values: 0.014, 0.000, 0.274, 0.011) and discouragement factors (Pvalues: 0.000, 0.828, 0.150, 0.000).DiscussionThe findings underscore key challenges in medical students’ specialty choices, including significant mentorship gaps, pervasive gender inequity, and family obligations. Addressing these issues is essential for improving career decision-making and ensuring a more balanced distribution of specialties within Pakistan’s medical workforce. Targeted interventions are needed to mitigate these barriers and support students in making informed career decisions.